2006
DOI: 10.1590/s0034-89102006000300018
|View full text |Cite
|
Sign up to set email alerts
|

Body dissatisfaction in Brazilian schoolchildren: prevalence and associated factors

Abstract: OBJECTIVE:To examine the prevalence of body dissatisfaction and associated factors in 8-to 11-year-old schoolchildren. METHODS:A cross-sectional study including children aged 8-to 11-years enrolled in public and private schools in Porto Alegre, Southern Brazil, was carried out from August to December, 2001. A total of 901 subjects were selected through cluster sampling. Participants answered a questionnaire aimed at measuring body dissatisfaction and self-esteem and questions about family and social pressures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
44

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 21 publications
(27 reference statements)
3
30
1
44
Order By: Relevance
“…The high prevalence of dissatisfaction was demonstrated among girls by overweight and among boys by leanness. Similar dissatisfaction data have also been reported by surveys of healthy children and adolescents in the same age range (13)(14)(15)(16)(17) . In these studies, body image dissatisfaction was present in 59 to 82% of participants; this rate may be age-related, as subjects in these age ranges express a substantial concern with body weight from a very early age (13) .…”
Section: Discussionsupporting
confidence: 86%
“…The high prevalence of dissatisfaction was demonstrated among girls by overweight and among boys by leanness. Similar dissatisfaction data have also been reported by surveys of healthy children and adolescents in the same age range (13)(14)(15)(16)(17) . In these studies, body image dissatisfaction was present in 59 to 82% of participants; this rate may be age-related, as subjects in these age ranges express a substantial concern with body weight from a very early age (13) .…”
Section: Discussionsupporting
confidence: 86%
“…Assim, essa insatisfação envolve diversos fatores que se inter-relacionam, podendo ser citados: percepção da expectativa dos pais e amigos para ser mais magro 4 , localização geográfica da residência (grandes centros urbanos ou cidades menores) 5 , depressão 6 e comportamentos de saúde (auto-estima, comportamento alimentar, uso de esteróides e dependência de exercício) 3,6 , percepção equivocada do peso corporal 7 , idade 6 , razões pessoais para querer perder peso (aparência, saúde ou estética) 8 e sexo 9,10 .…”
Section: Introductionunclassified
“…Enquanto alguns estudos sugerem que pessoas com excesso de peso apresentam maior insatisfação com a imagem corporal 10,11 , outros demonstram que mesmo naquelas com massa corporal adequada, a prevalência de insatisfação é bastante alta 4 , ou seja, a relação entre estado nutricional e insatisfação com a imagem corporal permanece não resolvida. As pesquisas que objetivaram verificar essa relação utilizaram apenas o índice de massa corporal (IMC) como medida de estado nutricional 4,6,[10][11][12] .…”
Section: Introductionunclassified
“…Likewise, other authors (22) found that most overweight and obese adolescents were more dissatisfied with their body image than eutrophic adolescents. Conversely, in another study (23) , 82% of the sample of schoolchildren aged between 8 and 12 years-old reported to be dissatisfied with their body image, regardless of BMI classification, which shows that, in this case, body image dissatisfaction was not associated with nutritional status.…”
Section: Discussionmentioning
confidence: 79%